Modelling Gravity changes and crustal deformation in active volcanic areas - Charco, Maria; F. Tiampo, Kristy; Luzón, Francisco; Fernández, José (Física de la Tierra, 2005)
Elastic half-space models are widely used to interpret displacements and gravity changes in active volcanic areas. Those models usually compute the displacement response to dilatational sources that simulate a change in pressure of the magma chamber. However, elastic-gravitational model allows one to compute gravity, deformation and potential changes due to pressurized cavities and intruded masses together. First, we interpret deformation and gravity change data in Long Valley caldera, California, by using both a classical elastic and an elastic-gravitational model. Our results show that intruded mass can not be neglected for interpretation of gravity changes while displacements are mainly caused by pressurization. Therefore, the intrusion mass together with the associated pressurization produces distinctive changes in gravity that could be used to interpret gravity changes without ground deformation or viceversa depending on what is the source playing the main role in modelling. Second, we model the source of inflation at Long Valley caldera using a Genetic Algorithm inversion technique and microgravity data (1982-1998). The results of the performed inversions fit gravity anomaly centered under the resurgent dome. The two source inversion suggest that the gravity change could be caused by a more spatially distributed source under the resurgent dome.